2018
DOI: 10.1002/jgh3.12047
|View full text |Cite
|
Sign up to set email alerts
|

Postpolypectomy prophylactic clip closure for the prevention of delayed postpolypectomy bleeding: A systematic review

Abstract: Delayed postpolypectomy bleeding (DPPB) is the most common complication of colonoscopic polypectomy. Prophylactic clipping after an uncomplicated polypectomy is increasingly used, but it is unclear if this results in the prevention of DPPB. This study aimed to review prophylactic clip use and its effect on the rates of DPPB. MEDLINE, Embase, and the Cochran Library were systematically searched for studies (1995–March 2017) that used prophylactic hemoclips and assessed DPPB as an outcome. Of 1402 articles ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This inference is a distinct advantage of our analysis, because previous systematic reviews were not powered enough to perform it. [9][10][11][30][31][32] Our analysis showed the clinical relevance of 2 main factors: polyp size and location, on both the absolute risk of PPB and the relative efficacy of clipping, as well as their hierarchical interaction. Our adjusted estimates attributed a nearly 2-fold increase-from 4.3% to 7.6%-in the risk of PPB for lesions !20 mm.…”
Section: Discussionmentioning
confidence: 76%
“…This inference is a distinct advantage of our analysis, because previous systematic reviews were not powered enough to perform it. [9][10][11][30][31][32] Our analysis showed the clinical relevance of 2 main factors: polyp size and location, on both the absolute risk of PPB and the relative efficacy of clipping, as well as their hierarchical interaction. Our adjusted estimates attributed a nearly 2-fold increase-from 4.3% to 7.6%-in the risk of PPB for lesions !20 mm.…”
Section: Discussionmentioning
confidence: 76%
“…49 In contrast, in a separate randomized trial in 1,098 patients undergoing polypectomy of nonpedunculated polyps ≥10 mm, there was no benefit with closure of mucosal defects using prophylactic endoscopic clipping in reducing the rate of delayed PPB, and this finding was consistent with that obtained for large polyps (≥20 mm). 50 Several systematic reviews and meta-analyses [51][52][53][54][55][56] have consistently shown a similar lack of benefit of prophylactic endoscopic clipping of mucosal defects of nonpedunculated polyps up to 19 mm, with inconclusive benefits for nonpedunculated polyps ≥20 mm. This heterogeneity in polyps ≥20 mm could be due to variations in the polyp location that have not been accounted for in most studies, as was reported in the previously mentioned randomized trial 49 in which a benefit was noted only in the proximal colon.…”
Section: Prevention Of Post-polypectomy Bleedingmentioning
confidence: 98%
“…Two meta-analyses found no benefit from prophylactic clipping. 63,64 One consistent feature of the negative trials has been minimal bleeding in the control group. There is also heterogeneity in the studies, with polyps of varying sizes, shapes, and pathologies using both standard HSP and EMR.…”
Section: Clips and Detachable Snares/loopsmentioning
confidence: 90%